Cytosolic domain of the type I interleukin-1 receptor spontaneously recruits signaling molecules to activate a proinflammatory gene. - Singh, R (1997)
Immediate postreceptor events activated by IL-1-IL-1R interaction remain undefined. We have initiated studies to identify candidate signal transducers that associate with the cytosolic domain (cd) of the IL-1R. Immunocomplex kinase assays demonstrated an IL-1-activated myelin basic protein kinase activity that coprecipitated with the IL-1R from rat mesangial, mouse EL-4, and HeLa cells. Using glutathione-S-transferase (GST) fusion proteins, HeLa cell lysates next were assayed for kinases that associated with IL-1R cytoplasmic sequences. A GST-IL-1R fusion protein containing the entire cd (amino acids 369-569; GST-IL-1Rcd) recruited a kinase activity in the absence and presence of IL-1 stimulation. In contrast, a GST-IL-1R membrane-proximal region mutant (amino acids 369-501; GST-IL-1RcdDelta), which lacks COOH-terminal amino acid residues required for nuclear factor-kappaB activation, poorly phosphorylated MBP. In gel, kinase assays demonstrated 63-, 83-, and 100-kD kinases that specifically coprecipitated with the HeLa IL-1R and the GST-IL-1Rcd, but not GST-IL-1RcdDelta. 35S-labeled proteins, with Mrs identical to the kinase activities, stably associated with GST-IL-1Rcd. Transient transfection assays of 293 cells were used to evaluate the functional significance of these findings. Simply increasing IL-1cd expression in 293 cells stimulated 5'-IL-6 flanking region-regulated CAT activity threefold above control, an effect blocked by the kinase inhibitors staurosporine and calphostin C. In summary, we have identified two previously unrecognized 63- and 83-kD kinases as well as a protein with an Mr similar to the recently cloned IL-1R-associated kinase, all of which associate spontaneously with the IL-1Rcd. Ectopic IL-1Rcd expression was sufficient to trigger cellular activation, suggesting that the extracellular domain of the intact receptor represses signal transduction until IL-1 is bound. Given that the IL-1Rcd signaling domain has been conserved in a functionally diverse group of transmembrane receptors, further characterization of this signaling process may define novel molecular mechanisms controlling cellular function and differentiation.